Literature Review: The Influence of Demographics, User Experience and E-Commerce Platforms In The Digital Business World - Astuti, Murni; Ganefri; Yulastri, Asmar (The Indonesian Journal of Computer Science, 2023)
The presence of digital technology has fundamentally changed the business landscape, and one of the most striking transformations is the birth of e-commerce. Online business has become a global phenomenon that is spurring economic growth, increasing the accessibility of products and services, and changing the way companies interact with customers. In this context, three main factors emerge as key elements influencing the success of an e-commerce business: superior user experience, wise pricing strategy, and a sophisticated e-commerce platform. This research aims to find out how demographics, user experience and platforms influence the digital business world. The research method used in this research is Systematic Literature Review (SLR) with a qualitative approach in a systematic review which is used to summarize research results that are descriptive qualitative in nature. The results of this research are that there is a significant influence between demographics and user experience because these three variables greatly influence customer purchases because they can be a comparison of various aspects of purchasing through platforms in the digital business world.